Trends Analysis of HIV Infection and Antiretroviral Treatment Outcome in Amhara Regional from 2015 to 2021, Northeast Ethiopia - Addisu T; Tilahun M; Wedajo S; Sharew B (HIV/AIDS: Research and Palliative Care, 2023)
Tseganew Addisu,1 Mihret Tilahun,2 Shambel Wedajo,3 Bekele Sharew2 1Department of Dental Medicine, School of Medicine, College of Medicine and Health Science, Wollo University, Dessie, Ethiopia; 2Department of Medical Laboratory Sciences, College of Medicine and Health Science, Wollo University, Dessie, Ethiopia; 3School of Public Health, College of Medicine and Health Science, Wollo University, Dessie, EthiopiaCorrespondence: Mihret Tilahun, Department of Medical Laboratory Science, College of Medicine and Health Sciences, Wollo University, PO. BOX: 1145, Dessie, Ethiopia, Tel +251- 920988307, Fax +251 333115250, Email tilahunmihret21@gmail.comBackground: The persistent efforts of HIV/AIDS epidemiology remain one of the world’s most important community health threats. To avoid becoming an epidemic, UNAIDS has set three 90% fast-track targets for 2020, and Ethiopia has also changed its implementation since 2015. However, the achievement targets in the Amhara region have yet to be evaluated at the end of the programme period.Objective: The aim of this study was to assess the Trends of HIV Infection and Antiretroviral Treatment outcome in Eastern Amhara Regional from 2015 to 2021, Northeast Ethiopia.Methods: A retrospective study was conducted by reviewing the District Health Information System from 2015 to 2021. The collected data includes the trend of HIV testing services, the trend of HIV positivity, the yield of HIV testing approaches, the number of HIV positive patients linked to HIV care and treatment or access to lifelong antiretroviral therapy, viral load testing coverage, and viral suppression. A descriptive statistic and trend analysis were computed.Results: A total of 145,639 people accessed antiretroviral therapy. The trend of HIV test positivity has been declining since 2015, peaking at 0.76% in 2015 and declining to 0.60% in 2020. A high level of positivity was reported in volunteer counselling and testing as compared with provider-initiated testing and counselling services. Following an HIV positive, there was an increase in linkage to HIV care and treatment. High suppression rates of viral load indicate testing coverage grew over time. The viral load monitoring coverage was 70% in 2021, with a viral suppression rate of 94%.Conclusion and Recommendations: The trend in achievement in the first 90s was not consistent with predefined goals (90%). On the other hand, there was good achievement in the second and third goals. Hence, intensified case-finding approaches to HIV testing should be strengthened.Keywords: HIV, antiretroviral treatment outcome, trends